Intramolecular Carbene C-H Insertion Reactions of 2-Diazo-2-sulfamoylacetamides - Chuqiang Que (Molecules, 2019)
The intramolecular C-H insertions of carbenes derived from 2-diazo-2-sulfamoylacetamides were studied. 2-Diazo-2-sulfamoylacetamides were first prepared from chloroacetyl chloride and secondary amines through acylation followed by sequential treatments with sodium sulfite, phosphorus oxychloride, secondary amines, and 4-nitrobenzenesulfonyl azide. The results indicate that: (1) 2-diazo-N,N-dimethyl-2-(N,N-diphenylsulfamoyl)acetamide can take the formal aromatic 1,5-C-H insertion in its N-phenylsulfonamide moiety to afford the corresponding 1,3-dihydrobenzo[c]isothiazole-3-carboxamide 2,2-dioxide derivative; (2) no aliphatic C-H insertions occur for 2-diazo-2-(N,N-dialkylsulfamoyl)acetamides; and (3) for 2-diazo-N-phenyl-2-(N-phenylsulfamoyl)acetamides, the formal aromatic 1,5-C-H insertion in the N-phenylacetamide moiety is favorable to afford the corresponding 3-sulfamoylindolin-2-one derivatives as sole or major products. The intramolecular competitive aromatic 1,5-C-H insertion reactions of 2-diazo-2-sulfamoylacetamides with aryl groups on both amide and sulfonamide groups reveal that the N-aryl substituents on acetamide are more active than those on sulfonamide. The chemoselectivity is controlled by electronic effect of the aryl group.